Developing a performance measurement system for public research centres - Deborah Agostino; Marika Arena; Giovanni Azzone; Martina Dal Molin; Cristina Masella (International Journal of Business Science & Applied Management (IJBSAM), 2012)
This study aims at developing a performance measurement system (PMS) for research and development (R&D) activities carried out by public research centres. Public research institutions are characterized by multiple stakeholders with different needs, and the management of R&D activities requires balancing the multiple goals of different stakeholders. This characteristic is a key issue in the process of construction of the PMS. Empirical evidence is provided by an Italian public research centre, where the researchers carried out a project aimed to develop a PMS following action research principles. This project gave the possibility to researchers to interact with different stakeholders and integrate their different information needs in a comprehensive set of key performance indicators (KPIs). As a result, multidimensional framework for measuring R&D performance in a public research centre is proposed and a set of Key Performance Indicators is developed, suggesting implications for academics and practitioners.
Keywords: 650; performance measurement; public research centres; stakeholders; accountability; decision-making